Critical - Cook, Robin 1940- (G.P. Putnam's Sons, 2007)
Angela Dawson, M.D., climb to the top was rough, but she returns to school to earn an MBA and starts a company, Angels Healthcare. With her controlling interest in three busy specialty hospitals in New York City and plans for others, Angela's future looks very bright.Then a surge of drug-resistant staph infections in all three hospitals devastates Angela's carefully constructed world.